2014
DOI: 10.1093/gji/ggt503
|View full text |Cite
|
Sign up to set email alerts
|

Resolution of non-double-couple components in the seismic moment tensor using regional networks—II: application to aftershocks of the 1999 Mw 7.4 Izmit earthquake

Abstract: We study potential non-double-couple (non-DC) components in aftershocks of the 1999 Izmit earthquake. The Izmit earthquake ruptured a ∼140-km-long segment of the North Anatolian Fault Zone in northwestern Turkey and was followed by the M w = 7.1 Düzce earthquake that extended the rupture further to the east. Focal mechanisms of Izmit aftershocks clearly indicate a segmentation of the rupture into several segments, one of which is the Akyazi Plain, a pull-apart structure, where significant non-DC components mig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
27
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 48 publications
(30 citation statements)
references
References 31 publications
2
27
0
Order By: Relevance
“…This pattern was also observed by Seeber et al (2000) who found highly diverse focal mechanisms reflecting normal faulting as well as strike slip mechanisms. Moment tensor solutions from Stierle et al (2014b) also indicate a normal faulting regime at the southern part of the Karadere fault stressing the influence of the nearby east-west extensional Akyazi pull-apart basin. Koulakov et al (2010) investigated the distribution of Vp, Vs and attenuation in the crust beneath the fault based on local earthquake tomography.…”
Section: Karadere Fault South (Cluster E) and Karadere Fault North (Cmentioning
confidence: 92%
“…This pattern was also observed by Seeber et al (2000) who found highly diverse focal mechanisms reflecting normal faulting as well as strike slip mechanisms. Moment tensor solutions from Stierle et al (2014b) also indicate a normal faulting regime at the southern part of the Karadere fault stressing the influence of the nearby east-west extensional Akyazi pull-apart basin. Koulakov et al (2010) investigated the distribution of Vp, Vs and attenuation in the crust beneath the fault based on local earthquake tomography.…”
Section: Karadere Fault South (Cluster E) and Karadere Fault North (Cmentioning
confidence: 92%
“…First of all, microcrack density in Table 1 suggests two possible Journal of Geophysical Research: Solid Earth 10.1002/2017JB014581 distinctions of AE events in shear fracturing compared to tensile fracturing. It is probably why some nearly pure shear aftershocks (with insignificant non-double-couple components) exhibit a larger magnitude than some other tensional aftershocks (with substantial positive non-double-couple components) in the 1999 Izmit earthquake (Stierle et al, 2014). Logically, the former will be accompanied by more seismic events.…”
Section: Implications To Seismic Activitymentioning
confidence: 99%
“…Shear cracks often propagate along the crystal boundaries leading to a damage zone 5 to 10 times wider than tensile cracks, which mainly propagate along and across crystal boundaries. Additionally, many seismic studies have explored the correlation between stress regimes (tensile or strike slip) and the non-double-couple components of the seismic events (Julian et al, 1998;Kwiatek et al, 2014;Stierle et al, 2014;Vavryčuk, 2002). Multiple microcracking zones oriented nearly parallel with the loading direction were also observed in the region between the preexisting flaw tips where a macroscale shear crack forms finally.…”
Section: Introductionmentioning
confidence: 99%
“…These segments are bounded by geometric fault complexities and discontinuities (e.g., jogs and fault bends) that act as barriers to rupture propagation [ Segall and Pollard , ; Barka and Kadinsky‐Cade , ; Wesnousky , ; Lettis et al , ; An , ]. Where possible, the reconstruction of the fault traces and boundaries at the surface is informed by seismotectonic studies of recent earthquakes (e.g., 1999 Izmit and Düzce seismic sequence) [ Gülen et al , ; Barka et al , ; Bohnhoff et al , ; Bulut et al , ; Pucci et al , ; Stierle et al , ] and historical surface ruptures [ Ambraseys and Jackson , ].…”
Section: Segmentation Modelmentioning
confidence: 99%